Designing multiple types of spatial and non spatial databases integration model using formal specification approach - Julaily Aida, Jusoh; Mustafa, Man; Mohd Shafry, Mohd Rahim; Mohammad, Zaidi (2012)
The aim of this paper is to develop the integration model of multiple types of spatial and non spatial database using formal specification approach. Previously, most developer prefers not to use formal specification (FS) approach in designing a database system. However, recently these approaches have been agreed by software developers as a complementary. This approach was able to reduce the overall development time and can be use to provide an unambiguous and precise supplement to natural language descriptions. Furthermore, it can be rigorously validated and verified leading to the early detection of specification errors or debugs during software development process. Correcting errors at the early development stage were found cheaper than modifying a delivered system. A FS could be verified in order to explore the consequences of this specification and potentially to find mistakes. After it has been done, a greater confidence arises in order to test the system according to the actual user requirement specification.